PEMILIHAN VARIETAS DAN PENGGUNAAN PUPUK UREA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAYAM (AMARANTHUS L.) - NI KOMANG BUDIYANI; I WAYAN SUKASANA; AMIRUL MUJADDID UMMAH (GANEC SWARA, 2022)
Spinach is one of the green vegetables that are widely developed in several countries. Spinach is also rich in various vitamins and minerals. One way of cultivating spinach can be used with the addition of fertilizers, one of which is urea fertilizer. Urea fertilizer makes plant leaves greener, lusher, and fresher. Superior varieties make a significant contribution to increasing the yield and growth of a plant. The research method used a Randomized Block Design (RAK) with a factorial pattern. The interaction between urea fertilizer dose treatment and variety (N x V) had a very significant effect (P < 0.01) on some of the observed parameters. The highest total plant fresh weight was obtained at 1.5 g urea fertilizer dose treatment on red variety (N3V2). of 73.00 g from the lowest yield on the treatment dose of Urea fertilizer with no fertilizer 0 g on the green variety (N0V1), which is 41.67 g.